A blessing or a curse? Climate change and political economy effects on the agricultural sector: empirical evidence from Sub-Saharan Africa - Nzabirinda Etienne; Nkurunziza Joseph; Mugenzi Martin (International Journal of Climate Change Strategies and Management)
Purpose – This study aims to investigate how climate change and political economy factors interact to influence agricultural productivity in Sub-Saharan Africa (SSA). It aims to determine whether climate change and political economy act as a blessing or a curse on agricultural productivity. This study also examines how temperature, rainfall, CO2 emissions and governance affect the agricultural sector. Design/methodology/approach – Data from FAO and World Bank datasets were used, and GMM models were applied to assess the impact of climate change and politico-economic factors on agricultural productivity in SSA. Findings – Results show an interaction between the change in climate and agricultural productivity in SSA as complex. Within the short-term, increased temperatures and precipitation moderately improve yields but have a long-term negative impact. The outcomes suggest that increasing temperature by 1% produces a 0.388 reduction in yield, while increased CO2 levels by 1% result in a 0.53 reduction. These results really highlight the efforts of nationally determined contributions in trying to reduce temperature increases and associated emissions. Furthermore, political stability enhances productivity by 0.512 for every 1% increase in the variable. Economic growth and fertilizer use are positively linked to yield, but trade openness negatively affects domestic production. Research limitations/implications – This study’s primary limitation is the exclusion of some SSA countries due to unavailable data for key variables, potentially limiting the generalizability of the findings. In addition, while the study identifies significant short- and long-run effects, it does not account for nonclimatic factors such as policy changes or technological innovations that could influence agricultural productivity. Future research could incorporate a broader set of countries and variables, as well as explore the role of technological adaptation and governance in enhancing agricultural resilience to climate change. Practical implications – Empowering water management, promoting climate-smart agriculture and drought-resistant crops are crucial to raise agricultural productivity in SSA. Transition to a green economy through carbon credit mechanisms and reforestation is also critical. In addition, effective governance, secure land rights and infrastructural development will create a conducive investment environment, leading to long-term agricultural development and resilience. Social implications – Climate change and political economy dynamics significantly shape agricultural productivity in SSA. Shifts in temperature, rainfall variability and rising CO2 emissions, combined with governance quality, influence food security, rural livelihoods and economic stability. The findings highlight the dual potential of these forces: they may exacerbate vulnerability or, with sound governance and adaptation, serve as catalysts for resilience and sustainable development in SSA’s agriculture. Originality/value – The empirical evidence set by this research into the influence of climate change on agricultural productivity in SSA adds to the literature that exists on how climatic and political variables combine in the agricultural sector of the region. Its results are of high importance for policies related to adaptation to the climate; notably those about devising strategies that shall enhance agricultural resilience against the shifting climatic condition.